2010
DOI: 10.1021/jm1006269
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Analogues of the α2-Adrenergic Blocker Atipamezole: Small Changes, Big Consequences

Abstract: We report the discovery of a new family of α(2) adrenergic receptor antagonists derived from atipamezole. Affinities of the compounds at human α(2) and α(1b) receptors as well as their functional activities at hα(2A) receptors were determined in competition binding and G-protein activation assays, respectively. Central α(2) antagonist activities were confirmed in mice after oral administration. Further studies on a selected example: (+)-4-(1a,6-dihydro-1H-cyclopropa[a]inden-6a-yl)-1H-imidazole, (+)-1 (F 14805)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 64 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…It could effectively trigger the release of cortical noradrenaline in mouse after acute systemic administration, which was 30‐fold more potent than fipamezole and atipamezole. Interestingly, it could substantially increase the blood pressure in pithed rat but exert minimal cardiovascular effect in intact and anesthetized rat, suggesting its opposed central and peripheral actions …”
Section: Imidazoles As Antineuropathic Agentsmentioning
confidence: 99%
“…It could effectively trigger the release of cortical noradrenaline in mouse after acute systemic administration, which was 30‐fold more potent than fipamezole and atipamezole. Interestingly, it could substantially increase the blood pressure in pithed rat but exert minimal cardiovascular effect in intact and anesthetized rat, suggesting its opposed central and peripheral actions …”
Section: Imidazoles As Antineuropathic Agentsmentioning
confidence: 99%
“…9), a potent antagonist of presynaptic a 2A C À1 receptors; however, it also stimulated vascular a 2 receptors, leading to substantial increase in blood pressure in the pithed rat. 29 The (+)-enantiomer of 18 is a potent partial agonist of GPR109a and reduces fatty acid levels in human adipocytes and mice. 30…”
Section: Bicyclohexanesmentioning
confidence: 99%
“…For example, Vacher and colleagues recently showed that cyclopropane‐containing compound 18 exhibited an affinity of two orders of magnitude higher to the α‐adrenergic receptor relative to the known drug Atipamezole (Figure 6). 25 In this context, the synthesized amines are the ideal candidates for the diversity‐oriented conformational‐restriction strategy 24e…”
Section: Discussionmentioning
confidence: 99%